A rice Serine/Threonine receptor-like kinase regulates arbuscular mycorrhizal symbiosis at the peri-arbuscular membrane. Issue 1 (December 2018) - Roth, Ronelle; Chiapello, Marco; Montero, Héctor; Gehrig, Peter; Grossmann, Jonas; O'Holleran, Kevin; Hartken, Denise; Walters, Fergus; Yang, Shu-Yi; Hillmer, Stefan; Schumacher, Karin; Bowden, Sarah; et al.
Abstract In terrestrial ecosystems most plant species live in mutualistic symbioses with nutrient-delivering arbuscular mycorrhizal (AM) fungi. Establishment of AM symbioses includes transient, intracellular formation of fungal feeding structures, the arbuscules. A plant-derived peri-arbuscular membrane (PAM) surrounds the arbuscules, mediating reciprocal nutrient exchange. Signaling at the PAM must be well coordinated to achieve this dynamic cellular intimacy. Here, we identify the PAM-specific Arbuscular Receptor-like Kinase 1 (ARK1) from maize and rice to condition sustained AM symbiosis. Mutation of riceARK1 causes a significant reduction in vesicles, the fungal storage structures, and a concomitant reduction in overall root colonization by the AM fungusRhizophagus irregularis . Arbuscules, although less frequent in theark1 mutant, are morphologically normal. Co-cultivation with wild-type plants restores vesicle and spore formation, suggesting ARK1 function is required for the completion of the fungal life-cycle, thereby defining a functional stage, post arbuscule development. The peri-arbuscular membrane (PAM) mediates mutually-beneficial nutrient exchange between plants and arbuscular mycorrhizal (AM) fungi. Here the authors identify ARK1, a PAM-specific receptor-like kinase from rice that sustains AM symbiosis post-arbuscule development.